2006
DOI: 10.1007/s11661-006-1085-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strontium on the microstructure, mechanical properties, and fracture behavior of AZ31 magnesium alloy

Abstract: The effect of strontium (Sr) on the microstructure, mechanical properties, and fracture behavior of AZ31 magnesium alloy and its sensitivity to cooling rate are investigated. Three phases-blocky-shaped Mg 17 Al 12 , acicular Mg 20 Al 20 Mn 5 Sr, and insular Mg 16 (Al,Zn) 2 Sr-are identified in the Sr-containing AZ31 alloys. With increasing cooling rate, the blocky-shaped Mg 17 Al 12 phase increases, the acicular Mg 20 Al 20 Mn 5 Sr phase diminishes, and the insular Mg 16 (Al,Zn) 2 Sr phase is refined and granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 19 publications
2
52
0
1
Order By: Relevance
“…Other than nucleants and solute, solidification conditions also significantly affect the grain size of cast components. [12][13][14][15] Moreover, the solidification conditions can also affect the morphology of intermetallic particles. [16,17] Magnesium alloys containing rare earth (RE) elements usually exhibit excellent mechanical properties.…”
Section: Grain Refinement Is Beneficial To Cast Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than nucleants and solute, solidification conditions also significantly affect the grain size of cast components. [12][13][14][15] Moreover, the solidification conditions can also affect the morphology of intermetallic particles. [16,17] Magnesium alloys containing rare earth (RE) elements usually exhibit excellent mechanical properties.…”
Section: Grain Refinement Is Beneficial To Cast Componentsmentioning
confidence: 99%
“…However, the grains became coarsened when the cooling rate was increased to 16.5 and 22.6 K/s (Figures 2(c) and (d)), contrary to general observations that grains become refined with increasing cooling rate. [7,13,14] The optical micrographs of Mg-10Gd-2Y alloys with 1 pct Al addition are shown in Figure 3. The grains were equiaxed with an irregular shape at a cooling rate of 1.4 K/s (Figure 3(a)).…”
Section: A Grain Sizementioning
confidence: 99%
“…Similar result was obtained by Yuan et al 17) In addition, Nam et al 18) also found that the modification efficiency of Sr to Mg 2 Si phase in the microstructure of containing-Si magnesium alloys was better than that of Sb element. The effect of strontium on the microstructure of AZ31 magnesium alloy was investigated by Zeng et al 19) The phase diagrams of Sr-containing magnesium alloys are important base for investigation on the compounds of Mg-Sr based alloys. However, only limited work has been done on the phase diagrams of magnesium alloys containing Sr. 7,20,21) In 2003, Koray et al 20) calculated the liquidus projection of the ternary Mg-Al-Sr system, and the calculated phase diagram exhibited substantial disagreement with the experimental data.…”
Section: Microstructure Of New Type Magnesium Alloys Containing Stronmentioning
confidence: 99%
“…The research results obtained by Lee et al 22) showed that the grain size of magnesium and its alloys with low Al content could be reduced by adding minor Sr, but the refinement efficiency for magnesium alloys with high Al content was not obvious. In addition, Zeng et al 19) reported that the refinement efficiency of Sr to AZ31 magnesium alloy was affected by cooling rate. For a given Sr addition, the grain size of AZ31 alloy decreased with the increase of cooing rate (Fig.…”
Section: Microstructure Of New Type Magnesium Alloys Containing Stronmentioning
confidence: 99%
See 1 more Smart Citation